Modulation of long-term and short-term plasticity in the dentate gyrus granule cells by activating the β-adrenergic receptors of the basolateral amygdala. (23rd April 2020) - Noorani, Seyedeh Kebria; Hojati, Vida; Ardeshiri, Motahareh Rouhi; Akbari, Esmaeil; Ehsani, Simin
Highlights: Clenbuterol administration into the BLA plays a role in long-term potentiation (LTP) and paired-pulse responses. Activation of beta-adrenergic receptors of the BLA with clenbuterol potentiates LTP induction in the dentate gyrus (DG). Activation of beta-adrenergic receptors of the BLA facilitates the paired-pulse response at 500 ms inter-pulse interval. Abstract: The beta-adrenergic receptors of the basolateral amygdala (BLA) are involved in modulating emotional memory formation in the hippocampus. The molecular mechanisms of this involvement are still unclear. In this study, we investigate the effects of the beta-adrenergic receptors of the BLA involvements during the major cellular mechanisms that underlie memory formation in hippocampal sub-regions. Wistar rats were injected with the selective beta receptor agonist, clenbuterol (15 ng/0.5 μl) bilaterally into the BLA. Then, the long-term potentiation (LTP) and the paired-pulse responses were recorded. Control rats were injected by saline at the same volume. Our data indicated that the injection of clenbuterol into the BLA area enhanced the amplitude of the population spike (PS) but not the slope of the excitatory postsynaptic potential (EPSP). In addition, short-term plasticity in the dentate gyrus (DG) region was significantly changed at 500 ms inter-pulse interval. These results suggest that the activation of the beta-adrenergic receptors of the BLA can improve LTP induction, which depends on the short-term plasticity with a mechanism related to the GABAergic transmission. Thus, it can be concluded that the adrenergic system of the BLA engages with long-term and short-term plasticity.